Two new species of Meriania (Melastomataceae) from eastern Ecuador - Fernández-Fernández, Diana M.; Jost, Lou; Dellinger, Agnes S. (Phytotaxa, 2020)
We describe two new species of Meriania (Melastomataceae), Meriania ardyae from Llanganates National Park and Meriania zunacensis from the Río Zuñac Reserve in Ecuador. Meriania ardyae is characterized by dark crimson petals, hypanthium and calyx with a dark purple coloration, young branches and internodes covered with a dense pubescence of violet-black hirsute trichomes and slightly dimorphic stamens. Meriania zunacensis is distinguished by conspicuous interpetiolar flaps, inflorescences with glomerulate flower clusters, large flowers with magenta petals, isomorphic stamens, and a fleshy, strongly curved style.